(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This research studied the effect of cutting conditions and cooling fluid on the surface roughness for Aluminum alloy2024 worked by a turning machine in dry and wet cutting cases. The work was performed with different spindle speeds and feed rates with a constant depth of cutting. The cooling fluid used in this work was emulsion water (water/oil). The results proved that the cutting conditions and the coolant have a significant effect to maintain the surface with a least roughness (Ra) possible even without the use of the coolant. On the other hand, the results showed that the feed rate was very effective factor compared to the spindle speed.